Love, Gender Relations, and Women’s Education in Louisa May Alcott’s “Anna’s Whim”—A Close Reading of Intertextual Allusions - Julia Nitz (European Journal of American Studies)
This paper explores how Louisa May Alcott, in her 1873 short story, “Anna’s Whim,” invokes a particular concept of love and conjugal bliss to express her stance on the relation between the sexes in direct response to ongoing discussions about the woman question and the role of education in her time. Alcott positions herself on these subjects by invoking a variety of authors and texts and then providing her own fictional response to them. Intriguingly, she situates her discourse on love, gender relations, and women's education intertextually within a broader transatlantic discussion of nineteenth-century notions of woman's proper sphere of action.